1993
DOI: 10.1021/ac00058a027
|View full text |Cite
|
Sign up to set email alerts
|

Determination of cations and anions by capillary electrophoresis combined with suppressed conductivity detection

Abstract: Capillary electrophoresis combined with suppressed conductivity detection is a highly sensitive and selective method for the determination of UVtransparent ionic species. Using direct injection techniques (no electrostacking), minimum detection limits for common organic and inorganic ions are in the rangeof 1-10 ppb. Suppressors are made from short ion-exchange membrane capillaries and are placed between the separation capillary and the detector cell. The suppressor is placed in the destination vial, which con… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
63
0

Year Published

1996
1996
2007
2007

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 128 publications
(63 citation statements)
references
References 5 publications
0
63
0
Order By: Relevance
“…Furthermore, a slow eluter when using IC may be a very fast one when using CE. Avdalovic et al (1993) showed that perchlorate can be eluted by CE at 10 min; meanwhile, bromide, chloride, and iodide all take more than 15 min by their method. Hauser et al (1995) used CE with a micro-ISE to quantitate as little as 10 µM perchlorate.…”
Section: Ion Chromatography and Capillary Electrophoresismentioning
confidence: 99%
“…Furthermore, a slow eluter when using IC may be a very fast one when using CE. Avdalovic et al (1993) showed that perchlorate can be eluted by CE at 10 min; meanwhile, bromide, chloride, and iodide all take more than 15 min by their method. Hauser et al (1995) used CE with a micro-ISE to quantitate as little as 10 µM perchlorate.…”
Section: Ion Chromatography and Capillary Electrophoresismentioning
confidence: 99%
“…In ion chromatography, very low detection limit at ppb (ng/mL) level can be reached by background depression. Introduction of background depression normally used in ion chromatography was also found effective in CE as demonstrated in the reports [27,28].…”
Section: Capillary Chip Electrophoresis With Conductivity Detectionmentioning
confidence: 97%
“…Similarly to ion-chromatography single-column and the suppressed one, introduction of suppressed conductivity detection to CE allows fot the decrease of the limit of detection for common organic and inorganic ions to the level 1 ± 10 ppb [180,181]. As is shown in Figure 9, the suppressor is made from a short ion-exchange membrane capillary and placed between the separation capillary and the ion-chromatography conductivity detector, with one of the conductivity electrodes being grounded.…”
Section: Conductivity Detection In Cementioning
confidence: 99%
“…Satisfactory functioning of such a detector was shown in the separation of inorganic ions (Fig. 9), carboxylic acids, low mobility of amine cations, and even in partial separation of two isotopes of chlorine [181]. In another approach conductivity detection can be used in a contactless mode.…”
Section: Conductivity Detection In Cementioning
confidence: 99%
See 1 more Smart Citation